2018
DOI: 10.3390/f9120754
|View full text |Cite
|
Sign up to set email alerts
|

Allocation Mechanisms of Non-Structural Carbohydrates of Robinia pseudoacacia L. Seedlings in Response to Drought and Waterlogging

Abstract: Climate change is likely to lead to an increased frequency of droughts and floods, both of which are implicated in large-scale carbon allocation and tree mortality worldwide. Non-structural carbohydrates (NSCs) play an important role in tree survival under stress, but how NSC allocation changes in response to drought or waterlogging is still unclear. We measured soluble sugars (SS) and starch in leaves, twigs, stems and roots of Robinia pseudoacacia L. seedlings that had been subjected to a gradient in soil wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 76 publications
1
8
2
Order By: Relevance
“…Under drought conditions, the ratio of soluble sugar to starch remained relatively stable, except for the increase observed in branches, and both soluble sugar and starch increased slightly. However, this result contrasts with previous studies which have reported that the ratio of soluble sugar to starch significantly increased [25], and the increase in soluble sugars was converted to starch [64]. This may have been due to the inhibition of growth and metabolism being much greater than photosynthesis rate in our study, which would result in the accumulation of starch in all organs.…”
Section: Effects Of Drought and Shading On Growth And Nsc Concentrationcontrasting
confidence: 99%
See 1 more Smart Citation
“…Under drought conditions, the ratio of soluble sugar to starch remained relatively stable, except for the increase observed in branches, and both soluble sugar and starch increased slightly. However, this result contrasts with previous studies which have reported that the ratio of soluble sugar to starch significantly increased [25], and the increase in soluble sugars was converted to starch [64]. This may have been due to the inhibition of growth and metabolism being much greater than photosynthesis rate in our study, which would result in the accumulation of starch in all organs.…”
Section: Effects Of Drought and Shading On Growth And Nsc Concentrationcontrasting
confidence: 99%
“…Our findings will be helpful in predicting the impact of climate change on P. massoniana growth.Non-structural carbohydrate (NSC), a carbon reserve for energy and biosynthesis, provides energy for physiological processes (e.g., metabolism, cell turgor maintenance, and embolism repair) [21,22] and plant growth [23]. Plants enriched with higher NSC concentrations can maintain metabolic functions for survival and long-term growth [22,24,25], and their resistance to stressful environments is increased [26]. Both drought and shading cause an imbalance in organic carbon supply and demand that results in a trade-off between plant growth and NSC storage [27][28][29][30][31], which in turn affects plant growth and stress tolerance [32,33].…”
mentioning
confidence: 99%
“…After harvesting, seeds were labeled for each provenance and deposited in paper bags in a refrigerator (at approximately +4 • C) until further analysis. Moreover, since water stress is known to induce both morphological and anatomical changes [50][51][52], seedlings were also studied [53]. The seedlings obtained from treated seeds were further analysed by being kept in the laboratory for three months, then taken outside in natural conditions; at the end of six months, morphological traits were measured: height, stem diameter and number of branches.…”
Section: Biological Materialsmentioning
confidence: 99%
“…Changes in global precipitation increase the frequency and intensity of extreme precipitation in humid areas, subsequently leading to frequent floods [1][2][3]. Floods induced by extreme precipitation expose trees to waterlogging stress, and cause root hypoxia and inhibit plant respiration, ultimately increasing the tree mortality [4][5][6]. This phenomenon is particularly universal in the river basins and estuarine deltas of tropical/subtropical areas [7][8][9].…”
Section: Introductionmentioning
confidence: 99%